Numerical study of the effect of soil texture and land use distribution on the convective precipitation - Göndöcs, Júlia; Breuer, Hajnalka; Horváth, Ákos; Ács, Ferenc; Rajkai, Kálmán (Hungarian Geographical Bulletin, 2015)
In this study the Weather Research Model is used to analyse the sensitivity of convection to soil texture and land use distribution based on a heavy precipitation event. Both characteristics aff ect the latent heat flux and the near surface temperature distribution which are related to buoyancy. The model defaults Food and Agriculture Organization (FAO) soil texture and USGS (United States Geological Survey) land use have been replaced with more accurate databases in Hungary: soil texture based on the Digital Kreybig Soil Information System (DKSIS), land use based on the COoRdination of INformation on the Environment (CORINE). Regarding to soil texture the main changes are related on one hand to clay loam diversification to silty clay, loam, silty loam and sandy loam affecting area over 40 percent of Hungary, and on the other hand reclassification of sandy loam to sand. The difference between USGS and CORINE land use is sporadic, but significant. It is found that the diurnal latent heat flux is the highest at 12 UTC, at this peak the spatial average difference in latent heat flux is +6.5 W/m2 and -4.3 W/m2 with respect to soil texture and land use change, while the absolute differences range from -70 W/m2 to +70 W/m2 in all cases. As a result temperature at 2 m on average increased by 0.1 °C during soil texture and decreased by 0.15 °C during land use database comparison; the absolute differences are a magnitude higher. When comparing simulations regarding temperature at 2 m over main soil types and main land use categories results indicate -3 °C to +0.5 °C difference. It is found that the modification of both the soil texture and the land use have sometimes a compensating effect on latent heat flux and temperature change. Decrease in latent heat flux results an increase in buoyancy affecting convective precipitation. The formation of precipitation is also affected by large scale advection, therefore, no systematic changes can be seen on daily precipitation distribution. In spite of this, results indicate shifts in precipitation bands with about 30 km, and formation of new storm cells. Locally the replacement of soil texture and land use information to a more accurate one produced ?8 mm/day differences in precipitation.